1998
DOI: 10.1001/archpsyc.55.9.809
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Age, Sex, and the Incidence of Dementia and Alzheimer Disease

Abstract: The acceleration of incidence rates for AD and dementia slows down with the increase in age, although we find no evidence of a rate decline. Women are at higher risk of developing AD than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
442
10
20

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 692 publications
(512 citation statements)
references
References 57 publications
40
442
10
20
Order By: Relevance
“…very advanced age has been considered controversial with respect to the increase in prevalence of dementia. This can be explained because studies typically do not include the very old 20 . however, ritchie 21 reported an exponential increase in dementia with age, which agrees with our data.…”
Section: Discussionmentioning
confidence: 99%
“…very advanced age has been considered controversial with respect to the increase in prevalence of dementia. This can be explained because studies typically do not include the very old 20 . however, ritchie 21 reported an exponential increase in dementia with age, which agrees with our data.…”
Section: Discussionmentioning
confidence: 99%
“…9,16,17,24 A prevalência de demência dobra a cada cinco anos de aumento da idade, indo de 3% aos 70 anos para 20-30% aos 85 anos. 16,24 Na Europa, estima-se uma prevalência uniforme de 6% para o problema para pessoas com 65 anos ou mais.…”
Section: Epidemiologia Da Demência Em Países Em Desenvolvimentounclassified
“…As taxas de incidência encontradas em Ibadan também são inferiores às taxas de incidência para demência e Doença de Alzheimer encontradas em outros estudos realizados na Europa e EUA. 9,17 Além da escassez de dados empíricos sobre a epidemiologia da demência em países em desenvolvi-mento, os pesquisadores envolvidos com esse tema enfrentam dificuldades metodológicas importantes. 4,7 Um dos problemas mais freqüentemente encontrado nos estudos populacionais sobre demência nos países em desenvolvimento é a utilização dos mesmos instrumentos para rastreamento e detecção de casos utilizados em estudos europeus e americanos.…”
Section: O Projetounclassified
“…Three covariates from the Indianapolis data were used: age of the subjects at each study wave, a binary indicator for sex and a three-level categorical variable indicating a subject's general cognitive functioning at study baseline screening phase (good, intermediate and poor). Epidemiological studies have shown that age and sex are risk factors for dementia [18]. The instrument used to evaluate cognitive functioning was shown to be a good predictor of dementia status [19].…”
Section: Covariate Dependent Hazard Ratesmentioning
confidence: 99%